Gamification-Based Learning Media in Object-Oriented Programming Subjects to Increase Learning Motivation of VHS Students - Elmunsyah, Hakkun; Rosyid, Harits Ar; Fitranti, Annisa; Setlhatlhanyo, Keiphe Nani (2021 7th International Conference on Electrical, Electronics and Information Engineering (ICEEIE), 2021)
The results of observations and interviews of learning media for Object-Oriented Programming subjects at Vocational high school (VHS) Malang City indicate a lack of innovation in the learning media used. Therefore, it is necessary to innovate learning media that can be accessed anywhere, anytime, and build engagement with students to foster student learning motivation. The concept of gamification in combining learning and games can be one of the best innovations to maximize the process. This development research uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The results showed that the product developed according to the learning media expert was stated in a very valid category. The material expert's assessment stated that it was in a valid category. In the feasibility test, the test results on the small group test subjects stated that the development results were in a very feasible category and the large group obtained a very feasible category as well. Measurement of students' learning motivation in small groups, got the "Good" category. In the large group, the score for measuring learning motivation was obtained in the motivation category at the "Good" level.